NEK2 Promotes Cell Proliferation and Glycolysis by Regulating PKM2 Abundance via Phosphorylation in Diffuse Large B-Cell Lymphoma - Zhou, Lingna; Ding, Liya; Gong, Yuqi; Zhao, Jing; Zhang, Jing; Mao, Zhengrong; Wang, Zhe; Zhang, Wei; Zhou, Ren (Frontiers in Oncology, 2021)
Diffuse large B-cell lymphoma (DLBCL) is the most frequent and commonly diagnosed subtype of NHL, which characterized by high heterogeneity and malignancy, and most of DLBCL patients are at advanced stages. The serine/threonine kinase NEK2 (NIMA-related kinase 2), a member of NIMA-related kinase (NEK) family that regulates cell cycle, is upregulated in a variety of malignancies including diffuse large B-cell lymphoma. However, the role and underlying mechanisms of NEK2 in DLBCL has seldom been discussed. In this study, we identified that NEK2 is upregulated in DLBCL compared to normal lymphoid tissues and overexpression of NEK2 predicted worse prognosis of DLBCL patients. Gene set enrichment analysis indicates that NEK2 might participate in regulating glycolysis. Knock down of NEK2 inhibited growth and glycolysis of DLBCL cells. The interaction between NEK2 and PKM2 was discovered by tandem affinity purification, and then was confirmed by immunofluorescence staining, coimmunoprecipitation and immunoprecipitation. NEK2 bounds to PKM2 and regulates PKM2 abundance via phosphorylation, which increase PKM2 stability. Xenograft tumor model check the influence of NEK2 on tumor growth in vivo. Thus, NEK2 could be the novel biomarker and target of DLBCL, which remarkably ameliorates the diagnosis and treatment of DLBCL.